High Burden and Trend in Nonadherence to Blood Pressure‐Lowering Medications: Meta‐Analysis of Data From Over 34 000 Adults With Hypertension in Sub‐Saharan Africa - Leopold N. Aminde; Valirie N. Agbor; Noah T. Fongwen; Calypse A. Ngwasiri; Clovis Nkoke; Miriam A. Nji; Anastase Dzudie; Aletta E. Schutte (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Nonadherence to blood pressure (BP)‐lowering medication is a strong predictor of poor BP control. Sub‐Saharan Africa has extremely low BP control rates (~10%), but it is unclear what the burden of medication nonadherence among Africans with hypertension is. This systematic review estimated the prevalence and determinants of nonadherence to BP‐lowering medications in Sub‐Saharan Africa. Methods and Results Multiple databases were searched from inception to December 6, 2023. Two reviewers performed independent screening, extraction, and quality assessment of studies. We pooled the prevalence estimates using random effects meta‐analyses and summarized the determinants using a narrative synthesis. From the 1307 records identified, we included 95 studies published between 1995 and 2023. The overall prevalence of nonadherence to BP‐lowering medication among 34 102 people treated for hypertension in 27 countries was 43.9% (95% CI, 39.2–48.6). There was no change in the prevalence of nonadherence over time. Nonadherence varied by measurement method and by median age (39.4%, ≥57 years versus 47.9%, <57 years). Socioeconomic and patient‐related factors were the most frequent factors influencing adherence. Active patient participation in management, accurate perceptions, and knowledge of hypertension and its treatment predicted good medication adherence, whereas high pill burden, medication cost, side effects, and comorbidities predicted poor adherence. Conclusions Two out of every 5 people are nonadherent to their BP treatment. With the African population projected to increase from 1.4 to ~2.5 billion by 2050, targeted strategies are urgently needed to optimize medication adherence in people with hypertension in Sub‐Saharan Africa.